Macular thickness analysis using optical coherence tomography data, stereopsis and binocular vision in premature infants who underwent retinal laser photocoagulation due to retinopathy of prematurity in an age-related perspective (Ukrainian Journal of Ophthalmology, 2024)
The purpose was to establish reference values for macular thickness, binocular vision, and stereopsis in premature infants aged 5-9 years and 10-13 years who underwent laser photocoagulation of avascular retinal zones due to retinopathy of prematurity (ROP); to assess and compare the data in an age-related perspective.Methods. Data from 24 premature infants who underwent ophthalmological examination, including optical coherence tomography, Titmus Stereo Fly Test, and the Worth 4 Dot Test, at ages 5-9 years and again at ages 10-13 years were analyzed. All children had undergone laser photocoagulation of avascular retinal zones due to ROP in infancy. Results. At ages 5-9 years, the mean central macular volume was 9.2 mm3, and the retinal thickness in the central fovea was 313.7 μm. At ages 10-13 years, the mean central macular volume was 9.1 mm3, and the retinal thickness in fovea was 320.8 μm. Normal binocular vision and stereopsis were observed in 79.2% and 33.3% of the children at the first time point, and in 87.5% and 45.8% at the second time point.Conclusions. No statistically significant difference in the central macular volume and macular thickness was detected between the two time points, (p>0.05). The thickest part of the macula was identified in the inner macula, followed by the outer macula, with the nasal quadrant being the thickest. Despite the anatomical peculiarities, high rates of binocular vision were observed at both time points, along with stereopsis at the second examination.
Keywords: retinopathy of prematurity; macular thickness; stereopsis; binocular vision